Alteridades Em Debate: Parahereges Ii De León Ferrari Na Pinacoteca Do Estado De São Paulo - Silva, Edy Carlos Leite Da [UNIFESP] (2017)
León Ferrari was an Argentine contemporary artist known for his controversial work, wich criticizes the western christian power and ideology. Among his many works of art, the Parahereges series, studied here with greater attention (specifically the Pareherege II), is an evidence of the artist's questioning and authentic character, within an apparently free art system, but wrapped by a society still faithful to catholic Church's mores, traditions and ideologies. Its provocative feature lies precisely in the encounter between sacred works of art, or images of saints, associated with inhuman atrocities committed by famous political systems of the present-day society, like Nazism . The trajectory of this research follows the historical path of his journey as an artist in a country that suffered one of the worst dictatorships in Latin America. Besides that, the formative process in the works of the series in question resulted from the artist's research on photomontage, which will be observed here under the bias of the German artist John Heartfield. In this respect, the philosopher Walter Benjamin's theories will serve as support and sustention to what is understood as political photomontage.